Challenges in online mathematics education for elementary schools: A teacher’s perspective from Indonesia - Ramdhani, Sendi; Nirmala, Sri Dewi; Nurcahyono, Novi Andri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
This study investigatesd the challenges of online mathematics education in Indonesian elementary schools during the COVID-19 pandemic, which exposed critical limitations in digital learning delivery. The research aimed to identify the most difficult mathematical topics to teach online, explore the effectiveness of digital tools used by teachers, and provide strategic recommendations. Using a cross-sectional survey method, the study involved elementary school teachers from various regions in Indonesia. Data were collected via a structured questionnaire containing both closed- and open-ended items, then analysed using descriptive statistics and thematic analysis. The findings showed that mathematics was the most challenging subject to teach online due to difficulties in demonstrating abstract concepts like geometry, fractions, and 3D figures. Teachers also faced obstacles in student engagement, timely feedback, and access to interactive teaching media. Video conferencing tools were most frequently used, followed by learning management systems and messaging apps. The study concluded that online mathematics learning required substantial improvement in terms of instructional design and teacher support. It was recommended that policymakers and schools invest in developing interactive, media-rich learning resources and provide training programs to enhance teacher readiness for future online or blended learning environments.